Farming Analysis and Marketing Strategy of Red Guava (Psidium guajava L.) in Karanganyar District - Khairrunnisa, Jihan; Rahayu, Endang Siti; Agustono, Agustono (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2020)
This study aimed to determine the feasibility of farming and identify internal and external factors in the marketing of red guava in Karanganyar District. The basic methods of this research are descriptive and analytical methods. The research location was chosen purposively in Karanganyar District, while the sampling of red guava farmers was done by using Snowball Sampling technique. The data analysis methods used are (1) Farming feasibility analysis by calculating NPV, IRR, Net B/C Ratio, and payback period, while (2) Marketing strategy was analyzed using IFE, EFE, Grand Strategy, and SWOT analysis. The results showed that the total cost of producing red guava was IDR 390,525,560 per hectare with benefits obtained by farmers was IDR665,129,380 per hectare. The calculation results of the feasibility of red guava farming on NPV, IRR, Net B/C Ratio, and payback period were respectively IDR 66,717,379.00 per Ha, 22.88%, 1.50, and 6 years, indicating that red guava farming in Karanganyar District is worthy. Based on the results of Grand Strategy matrix analysis, it is known that the difference between the strength and weakness factors was 1.427 and the opportunity factor with the threat was 1.829, placing red guava in quadrant I. The resulting alternative strategies were in the SO (Strengths-Opportunities) strategy.